Conservation of the primary structure, organization, and function of the human and mouse beta-globin locus-activating regions. - Moon, A M (1990)
DNA sequences located in a region 6-18 kilobases (kb) upstream from the human epsilon-globin gene are known as the locus-activating region (LAR) or dominant control region. This region is thought to play a key role in chromatin organization of the beta-like globin gene cluster during erythroid development. The beta-globin LAR activates linked globin genes in transiently or stably transfected erythroleukemia cells and in erythroid cells of transgenic mice. Since the human beta-globin LAR is functional in mice, we reasoned that critical LAR sequence elements might be conserved between mice and humans. We therefore cloned murine genomic sequences homologous to one portion of the human LAR (site II, positions -11,054 to -10,322 with respect to the human epsilon gene). We found that this murine DNA fragment (mouse LAR site II) and sequences homologous to human LAR sites I and III are located upstream from the mouse beta-like globin gene cluster and determined that their locations relative to the cluster are similar to that of their human counterparts. The homologous site II sequences are 70% identical between mice and humans over a stretch of approximately 800 base pairs. Multiple core sequences with greater than 80% identity were present within this region. Transient and stable transfection assays of K562 erythroleukemia cells demonstrated that both human and mouse LAR elements contain enhancer activity and confer hemin inducibility on a linked human gamma-globin promoter. These results suggest that primary structural elements--and the spatial organization of these elements--are important for function of the beta-globin LAR.